2015
DOI: 10.1016/j.fertnstert.2015.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Profiling signaling proteins in human spermatozoa: biomarker identification for sperm quality evaluation

Abstract: This study contributed toward establishing a biomarker "fingerprint" to assess sperm quality on the basis of molecular parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 92 publications
(84 reference statements)
0
30
0
Order By: Relevance
“…On grouping of bulls based on PEBP4 expression, the total motile spermatozoa, type-A sperm, and fructose uptake were higher in PEBP4 expressing bulls indicating its significance in sperm functional activity. As the fructose uptake was higher in protein present group, the PEBP4 also might regulate spermatozoa metabolic activity and motility through protein phosphorylations signaling cascades (Silva et al, 2015). Hence, PEBP4 in spermatozoa might regulate the motility by switching the pathways connected to sperm energy consumption.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On grouping of bulls based on PEBP4 expression, the total motile spermatozoa, type-A sperm, and fructose uptake were higher in PEBP4 expressing bulls indicating its significance in sperm functional activity. As the fructose uptake was higher in protein present group, the PEBP4 also might regulate spermatozoa metabolic activity and motility through protein phosphorylations signaling cascades (Silva et al, 2015). Hence, PEBP4 in spermatozoa might regulate the motility by switching the pathways connected to sperm energy consumption.…”
Section: Discussionmentioning
confidence: 76%
“…This is the first study reporting the localization of PEBP4 in the principal piece of ejaculated spermatozoa and a positive association of PEBP4 expression with sperm motility. As the fructose uptake was higher in protein present group, the PEBP4 also might regulate spermatozoa metabolic activity and motility through protein phosphorylations signaling cascades (Silva et al, 2015). The PEBP4 is also a member of RAF kinase inhibitory protein (RKIP1) family inactivating Raf-1/MEK/ERK by exhibiting scaffolding of proteins regulating apoptosis (Yeung et al, 1999;Hickox et al, 2002).…”
Section: Discussionmentioning
confidence: 80%
“…The PPAR γ agonist rosiglitazone induced clear improvements in mitochondrial function, and reduced caspase 3 activity, these effects also linked to increased phosphorylation of Akt. Previous reports indicate the importance of Akt phosphorylation in sperm function [15, 16, 52, 53], and recently a link between PPARγ agonists and Akt phosphorylation in human [22] and pig spermatozoa [23] has been reported. Moreover strategies to maintain Akt phosphorylated in spermatozoa have proven to be successful in human sperm cryopreservation [52, 54]…”
Section: Discussionmentioning
confidence: 99%
“…While H 2 S decreases phosphorylation by MAPK in the testis [39], NO activates MAPK participating in the tight-junction dynamics of Sertoli cells [106]. This MAPK regulation by H 2 S and NO may also be of interest regarding sperm cells, as it is a crucial pathway affecting sperm motility, morphology, and capacitation [57,107]. For the first time in human spermatozoa, Silva et al [107] identified JNK, which represent a subfamily of MAPKs also referred to as stress-activated protein kinases (SAPKs), as they are activated by phosphorylation under stress conditions (e.g., oxidative stress).…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%
“…This MAPK regulation by H 2 S and NO may also be of interest regarding sperm cells, as it is a crucial pathway affecting sperm motility, morphology, and capacitation [57,107]. For the first time in human spermatozoa, Silva et al [107] identified JNK, which represent a subfamily of MAPKs also referred to as stress-activated protein kinases (SAPKs), as they are activated by phosphorylation under stress conditions (e.g., oxidative stress). The same authors observed a negative correlation of JNK phosphorylated levels with total and progressive motility.…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%